Terpenoids from leaves of Viburnum sambucinum Reinw. ex. Blume (Caprifoliaceae) - Tra, Nguyen Thanh; Ngan, Truong Bich; Nam, Vu Van; Thao, Do Thi; Litaudon, Marc; Mai Huong, Doan Thi; Hung, Nguyen Van; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Six compounds were isolated from the leaves of Viburnum sambucinum Reinw. ex Blume (Caprifoliaceae). The structures of the isolates were determined by spectroscopic analysis including MS and NMR. Accordingly, the isolated compounds were identified as a-amyrin (1), ursolic acid (2), 3β,28-dihydroxy-urs-12-ene (3), oleanolic acid (4), 16β-hydroxylup-20(29)-ene-3-one (5) and trans-2-phyten-1-ol (6).